Influence of social responsibility management on the configuration of management control in Moroccan companies - Nabil Seghyar; Mounir Gouiouez; Mohamed Achraf Nafzaoui; Meryem Amane (Problems and Perspectives in Management)
In contemporary managerial aspects, corporate social responsibility (CSR) plays an important role in the societal commitment of businesses. The objective of this study is to clarify the level of influence of corporate social responsibility management on the configuration of management control systems. In this perspective, a quantitative empirical study was conducted with 77 Moroccan companies recognized for their CSR practices by the General Confederation of Moroccan Enterprises, demonstrating their commitment to social and environmental responsibility. Data were collected through a structured questionnaire survey, offering significant insights into the effect of CSR management on management control systems. The results showed that certain aspects of CSR management significantly influence the configuration of management control, while others have no notable impact. Governance (β = 0.178, p < 0.05), consumer protection (β = 0.244, p < 0.05), and community development (β = 0.107, p < 0.05) have a positive effect, as does the CSR strategy (β = 0.393, p < 0.05), which has the greatest impact. This indicates that companies integrating CSR into their strategy generally adopt a more structured management system. On the other hand, working conditions and relationships (β = –0.019, p > 0.05) and environmental issues (β = –0.012, p > 0.05) did not show a significant effect, suggesting a limited integration of these aspects into corporate management.